Role of cytomorphology in the diagnosis of sarcoidosis in subjects undergoing endobronchial ultrasound-guided transbronchial needle aspiration - Muthu, Valliappan; Gupta, Nalini; Dhooria, Sahajal; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Aggarwal, Ashutosh Nath; Agarwal, Ritesh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: The role of cytomorphology in differentiating sarcoidosis from tuberculosis is not fully elucidated. Herein, we evaluate the utility of cytological features in differentiating between these two diseases in subjects undergoing endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA). Methods: Retrospective analysis of subjects who underwent EBUS-TBNA and had a final diagnosis of sarcoidosis or tuberculosis. The final diagnosis was based on the clinicoradiological features, microbiology and clinical course during follow-up (including response to treatment) at six months. A cytologist blinded to the clinical details and microbiology examined the aspirates. The primary outcome was the diagnostic accuracy of cytologist’s impression to diagnose sarcoidosis as compared to the final diagnosis. Results: 179 (145 sarcoidosis, 34 tuberculosis) subjects were included. Granuloma was identified in 135 (75.4%) subjects; amongst these, the cytologist made a correct diagnosis in 62.2% cases, misdiagnosed 28.9% cases, and in 8.9% cases differentiating sarcoidosis from tuberculosis was not possible. The sensitivity, specificity, positive and negative predictive values (PPV and NPV) of the cytologist in diagnosing sarcoidosis was 62%, 64%, 90%, and 25%, respectively. The identification of a non-necrotic granuloma, along with a negative TST and the lack of endosonographic features favouring tuberculosis (heterogeneous echotexture and coagulation necrosis sign), provided the best specificity (97%) and PPV (99%) to diagnose sarcoidosis. Conclusion: Sarcoidosis cannot be reliably differentiated from tuberculosis based on cytomorphology alone. A combination of clinical features, endosonography, cytology and microbiology is required for accurate diagnosis.